PROYEKSI PRODUKSI DAN KONSUMSI TELUR AYAM RAS DI PROVINSI LAMPUNG - Asih Mityas Lestari; Agus Hudoyo; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
Poultry egg is one of the important animal protein resource.  Consequently, their availability in a society has to be predicted for several years.  In Lampung Province, the local government  forecasts the poultry egg production just for one year.  It causes the production of poultry egg, as well as their availability, is unknown for long term. Therefore, the aim of this study is to project  the production and to project the consumption of the poultry egg.  Both projections are compared in order to know its sufficiency. The prediction was done by the ordinary least square method with the time series data 2000-2013.   The result showed that the average product (AP) was 16.75 kgs/head/year. However, during the epidemic of the avian infulenza (2003-2007), the AP had been decreasing,  i.e. 15.99 kgs/head/year. The poultry egg production in 2013 was 51.39 thousand tons and the average growth rate was 3.64% per year.  Meanwhile, the poultry  egg consumption of Lampung Province  in 2013 was 51.33 thousand tons and the average growth rate was 2.48% per year.  Since the growth rate of production is higher than the growth rate of consumption, the production will be larger than the consumption starting in 2026. Key words: consumption, poultry egg, production, projection